2017
DOI: 10.26444/aaem/76937
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum selenium and zinc concentrations versus profibrotic and proangiogenic cytokines (FGF-19 and endoglin) in patients with alcoholic liver cirrhosis

Abstract: Relationships between serum selenium and zinc concentrations versus profibrotic and proangiogenic cytokines in patients with alcoholic liver cirrhosis. Ann Agric Env Med. 2017; 24(3): 544-548. doi: 10.26444/aaem/76937 Abstract Introduction and objective. Liver cirrhosis is a disease involving the liver parenchyma, which is characterised by fibrosis. and impaired architectonics of the parenchyma with regenerative nodules. The aim of the study was to determine the relationship between stage of alcoholic liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Selenium deficiency is often seen in ALD [ 41 ]. It has been shown that the level of selenium is lower in the group of patients with alcoholic liver cirrhosis compared to healthy ones, and it decreases proportionally with the degree of liver fibrosis [ 42 ]. The lowest concentration of serum selenium among liver diseases is found in HCC [ 18 ].…”
Section: Seleniummentioning
confidence: 99%
“…Selenium deficiency is often seen in ALD [ 41 ]. It has been shown that the level of selenium is lower in the group of patients with alcoholic liver cirrhosis compared to healthy ones, and it decreases proportionally with the degree of liver fibrosis [ 42 ]. The lowest concentration of serum selenium among liver diseases is found in HCC [ 18 ].…”
Section: Seleniummentioning
confidence: 99%
“…Selenium is an important component of antioxidant-glutathione peroxidase and thus it has been broadly used in the clinic due to its antioxidant property. Abnormal metabolism of selenium has been reported in a growing body of research, which suggested that low selenium level is a common feature of patients with ALD[ 52 ]. Selenium metabolic disorder may lead to liver dysfunction[ 52 , 53 ].…”
Section: Mineral Malnutrition In Aldmentioning
confidence: 99%
“…Abnormal metabolism of selenium has been reported in a growing body of research, which suggested that low selenium level is a common feature of patients with ALD[ 52 ]. Selenium metabolic disorder may lead to liver dysfunction[ 52 , 53 ]. However, the involvement of selenium depletion in the pathogenesis of ALD has not been fully defined.…”
Section: Mineral Malnutrition In Aldmentioning
confidence: 99%
“…In contrast to these results, the study of Prystupa et al showed the lowest concentration of Sol-ENG in patients with decompensated alcoholic liver cirrhosis and the highest in the control group. Moreover, their study demonstrated that the independent factors affecting the Sol-ENG level were the concentration of bilirubin, INR, and duration of alcohol abuse [123].…”
Section: Endoglin In the Pathogenesis Of Hcc—experimental And Clinmentioning
confidence: 99%